Out of office: the big problem and bigger promise of working from home - Petersen, Anne Helen; Warzel, charlie (Australia & UK, Scribe Publication, 2022)
"The past two years have shown us that there may be a new path forward, one that doesn't involve hellish daily commutes and the demands of jam-packed work schedules that no longer make sense. But how can we realize that future in a way that benefits workers and companies alike? Based on groundbreaking reporting and interviews with workers and managers around the world, Out of Office illuminates the key values and questions that should be driving this conversation: trust, fairness, flexibility, inclusive workplaces, equity, and work-life balance. Above all, they argue that companies need to listen to their employees--and that this will promote, rather than impede, productivity and profitability. As a society, we have talked for decades about flexible work arrangements; this book makes clear that we are at an inflection point where this is actually possible for many employees and their companies. Out of Office is about so much more than zoom meetings and hybrid schedules: it aims to reshape our entire relationship to the office."
Published by arrangement with Alfred A. Knopf, an imprint of Knopf Doubleday Publishing Group, a division of Penguin Random House LLC.
Includes index
nmn, 23/12/2022
Loans
Keywords: Telecommuting; Family & relationships; Business & Economics - Workplace Culture; Social Science - Anthropology - Cultural; Business & Economics - Office Management; Family & Relationships - General; Business & Economics - Management; Self-help / Self-management / Time Management; Business & Economics - Home-based Businesses; History / Social History; Psychology - Industrial & Organizational Psychology; Business & Economics - Careers; Business & Economics - Labor; Business & Economics - Business Ethics; Telecommuting; Office & workplace; Society & culture: general; Working patterns & practices; Management: leadership & motivation; Sociology: family & relationships; Business & Management; Time management; Ethical & social aspects of IT; Office management; Social & cultural history; History of ideas; Social attitudes; Occupational & industrial psychology; Population & demography; Sociology: work & labour; Advice on careers & achieving success; Business ethics & social responsibility